2016
DOI: 10.1016/j.cemconcomp.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological interpretation of the shear behavior of reinforced Engineered Cementitious Composite beams

Abstract: This paper describes an experimental investigation of the shear behavior of beams consisting of steel Reinforced Engineered Cementitious Composites (R/ECC). This study investigates and quantifies the effect of ECC's strain hardening and multiple cracking behavior on the shear capacity of beams loaded in shear. The experimental program consists of R/ECC beams with short (8 mm) randomly distributed Polyvinyl Alcohol (PVA) fiber and conventional Reinforced Concrete (R/C) counterparts for comparison with varying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…ECC's strain hardening and multiple cracking behavior on the shear capacity of beams loaded in shear were investigated by experiments [84]. Results exhibited that ECC was similar to steel reinforcements for improving the shear capacity of beams.…”
Section: Shear Performancementioning
confidence: 99%
“…ECC's strain hardening and multiple cracking behavior on the shear capacity of beams loaded in shear were investigated by experiments [84]. Results exhibited that ECC was similar to steel reinforcements for improving the shear capacity of beams.…”
Section: Shear Performancementioning
confidence: 99%
“…20 In addition, Han et al 20 also provided a similar idea to account for the Poisson effect by which local strains were converted into equivalent strains with a project matrix. The biaxial strains of ECC in Equation (16) are converted into uniaxial strains as follows:…”
Section: Relationship Between Biaxial Strains and Uniaxial Strainsmentioning
confidence: 99%
“…In addition to the remarkable improvement in the tensile ductility, various experiments demonstrated that obvious improvement was observed in the performance of shear‐critical ECC specimens . Therefore, ECC is being considered as the substitute of conventional concrete and creatively applied in seismic resistant structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear behaviors of ECC material and structure have been studied and the results demonstrate that the pseudo-strain-hardening tensile properties of ECC materials can be successfully translated into an advantageous structural shear response [11,12]. It was found that the ECC significantly enhanced the shear behavior of the short span beam under cyclic loading [13].…”
Section: Introductionmentioning
confidence: 99%